Batch and Flow injection Spectrophotometric Methods For Determination of Folic acid in Pharmaceutical Preparations using Cerium(IV) ammonium sulphate(CAS) as an oxidant. - Baban, Shirwan Omer; Azeez, Kurdistan F. (Sulaimani Journal for Pure and Applied Sciences, 2018)
A simple, rapid and sensitive batch and flow injection spectrophotometric methods have been developed for the determination of folic acid (FA) in pure form and in its pharmaceutical preparations. The proposed methods involve the addition of a measured excess of cerium (IV) ammonium sulphate (CAS) in acidic medium followed by determination of unreacted CAS by reacting with a fixed amount of methylene blue (MB) and measuring the absorbance at 665 nm. The optimum reaction conditions and other analytical parameters have been evaluated. Linearity was observed from 1-10 and 4.0-20.0 μg/ml folic acid by batch and flow injection procedures, respectively. Statistical analysis of the results and comparison with results by the British Pharmacopoeia method are also reported.
Keywords: Spectrophotometric Folic acid; Flowinjection; Methylene blue Cerium IV ammonium sulphate